Wireless Mesh Networks for IoT and Smart Cities: Technologies and Applications - Davoli, Luca; Ferrari, Gianluigi (Institution of Engineering & Technology, 2022)
Covering new developments and state-of-the-art research in Wireless Mesh Networks (WMNs), this edited book is a useful reference for ICT networking engineers, researchers, scientists, engineers, advanced students and lecturers in both academia and industry working on Wireless Communications and WMNs.
Keywords: Wireless communication systems -- Design and construction.; Internet of things.; Smart cities.; elektronické knihy; electronic books